Dynamic Mechanical Performance of Natural Fiber Reinforced Composites: A Brief Review - Siva Deeraj, Battula Durga; Joseph, Kuruvilla; Jayan, Jitha Santhakumari; Saritha, Appukuttan (Applied Science and Engineering Progress, 2021)
Natural fiber reinforced polymer composite is a much focused area of study owing to its environmentally friendly nature and good mechanical properties. These composites offer comparable mechanical properties to that of steel and other composite materials. Dynamic mechanical analysis is a widely used technique to investigate the mechanical performance of fiber reinforced composites at a wide range of temperatures. Using this technique, the thermal transitions and damping properties of fiber reinforced composites can be studied. These natural fiber composites are widely employed in structural applications in many industries. Here, in this short review we have presented the recent works on the dynamic properties of natural fiber reinforced composite materials with an essence of the influencing factors.